(untitled) (Economic and Political Thought, 2013)
The concept of a great power in the science of international relations originates from a realistic paradigm based on the idea of power as a foundation of international relations. The analysis based only on this paradigm seems to narrow the real research space. A presentation of the issue of countries being great powers in an economic context may be an interesting proposal in the analysis of change processes and development tendencies in international relations. As an interdisciplinary research instrument, it lets us treat economic and political processes in an integral way. The article makes an attempt to analyze the historical type of an economic great power. The empiric, valuable research material was provided by the history of Carthage, Venice and England. The research results can serve as an instrument to explain present phenomena and mechanisms taking place in the international environment.